Three-Dimensional Printed Flow Phantom Model of the Carotid Artery in Preterm Infants: Vessel Lumen Diameter Measurements Using Different Printing Materials - Pereira, Sujith S.; Reeves, Jonathan; Birch, Malcolm; Ali, Ahmed S; Kempley, Stephen T.; Sinha, Ajay K (British Journal of Healthcare and Medical Research, 2025)
Background: Diameter forms an integral part of blood flow measurement. This study aimed to explore different three-dimensional (3D) printed materials to develop flow phantom models of the carotid artery in preterm newborn infants and to investigate best materials for diameter measurement validation. Methods: We produced a 3D printed Doppler flow phantom model with vessel lumen diameter of 2.0 mm with varying vessel characteristics using data from 21 preterm infants (right carotid vessel lumen diameter, wall thickness, blood flow measurements using Doppler ultrasound and distance of the carotid artery from skin surface) examined for research or clinical purposes. Flow phantom vessel lumen diameters were measured by a single operator blinded to flow phantom diameter. Results: 15 diameter measurements were performed. Ultrasound measured vessel lumen diameter measurements resulted in underestimation of the true lumen diameter. The measured mean (SD, range) diameter was 0.163 (0.105, 0-0.420) mm. This study found that difference in vessel lumen diameter measurements were least with the hybrid material (FLXA9895-DM) with shore value of 95 in matte finish. Vessel wall thickness was systematically overestimated in the majority of the measurements {Anterior wall thickness, mean(SD, range) 0.145(0.081, 0.020–0.300) mm and posterior wall thickness, mean(SD, range) 0.103(0.117, minus 0.100–0.370) mm}. Conclusion: We successfully produced a 3D printed flow phantom model of the carotid artery in preterm infants with varying vessel characteristics and identified flow phantoms that produced the least difference in ultrasound measured vessel lumen diameter measurements. Researchers and clinicians can use this information for further studies involving ultrasound diameter measurements.